Ichthyosiform lesion at birth demystifying familial short stature - Chanchal Kumar; Sindhu Sivanandan; Nishad Plakkal (Wolters Kluwer Medknow Publications, 2021)
Conradi-Hünermann syndrome is a rare genetic condition characterized by skeletal malformations, skin abnormalities, cataracts and short stature. We report a term female infant presenting with a diffuse ichthyosiform erythroderma at birth. Physical examination also showed sparse lusterless hair with cicatricial alopecia, dystrophic nails, facial dysmorphism, and flexion contracture of fingers. Radiological examination revealed a shortening of the right femur and humerus, vertebral defects, scoliosis, and epiphyseal stippling of long bones on the right side. The infant's sister and mother had short stature and bony joint swellings. A clinical diagnosis of X-linked Conradi-Hünermann syndrome was considered based on clinical suspicion and radiological survey. Dermatologists and pediatricians should consider this diagnosis in children with suggestive features.